Application of microCT scanning in the recovery of endo-skarn associated scheelite from the Riviera Deposit, South Africa. (15th January 2018) - Rozendaal, Abraham; Le Roux, Stephan G.; du Plessis, Anton
Graphical abstract: Highlights: Scheelite recovery is studied using traditional XRF supported by microCT. Ore grade determination in floats and sinks determined from microCT. Scheelite particle size distributions determined in floats and sinks. MicroCT assessed in comparison to traditional grade analysis. Abstract: The granite-hosted Riviera W-Mo-REE deposit is an approximately 40 million ton low grade (∼0.2% WO3 ) endo-skarn resource and contains disseminated scheelite as the principle ore. Scheelite is strongly zoned and has a molybdenum-rich core and depleted rim. Separation of the high-demand low-molybdenum scheelite does not appear possible. The high density contrast between scheelite (ρ = 6.1) and gangue (ρ = 2.7) allows separation by gravity on tables, wet or dry spirals and heavy medium liquids. In the present laboratory study the latter method was used as a pre-concentration stage and yielded at best a ∼50% scheelite recovery of the −1 mm size fraction. The generally fine grain size of the liberated grains and considerable loss to the −45 µm fraction is a function of the friable nature of scheelite and possible overgrinding. The influence of this mineralogical characteristic on scheelite recovery will have to be accommodated in the beneficiation in particular the comminution stage, of the deposit in the future. As a complimentary study MicroCT scanning was applied as a relatively new analytical tool to evaluate the beneficiation results obtained. The method studied both sinks and floats of the various size fractions and allowed quantification of scheelite grain size distribution and calculation of ore grade of the coarse fractions. MicroCT images displayed the textural relationships between the ore and gangue minerals and the degree of scheelite liberation. This analytical tool proved useful in the present study and the results indicate that it can be applied to similar ore beneficiation studies.